Analysis of Accounting Implementation for Small and Medium Enterprises - Kariyoto Dr (Jurnal VOK@SINDO, 2015)
Accounting practices is the solution of the problems that often occur in Small and Medium Enterprises (SMEs), namely financial management problems. Accounting is used as a standard to facilitate SMEs in making the financial statements that can be accounted for and understood by the external and internal parties. Accounting practices should have been known or even practiced by SMEs. The purpose of this study is then to know and what kind of accounting practices are done by SMEs and to analyze compliance with the Principles of Financial Accounting Standards (PSAK). This type of research is a qualitative study with a descriptive approach. The data are obtained from interviews and observations. Informants in this study are 5 people consisting of 3 owners and 2 operational managers of SMEs in Pandanwangi. The results reveal that the financial statements of SMEs are still modest which is done by recording transactions that often occur in the business and PSAK are still not understood by SMEs. This eventually has been affected by insufficient educational background and lack of socialization or training from the government or agencies that are in charge of SMEs activities. As a result, the importance of PSAK still cannot be understood well. Regarding this, SMEs are expected to apply financial statements based on PSAK later.